Robust Yaw Stability Controller Design and Hardware-in-the-Loop Testing for a Road Vehicle - Bilin Aksun Güvenç; Levent Güvenç; Sertac Karaman (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Unsymmetrical loading on a car like mu-split braking, side wind forces, or unilateral loss of tire pressure results in unexpected yaw disturbances that require yaw stabilization either by the driver or by an automatic driver-assist system. The use of two-degrees-of-freedom control architecture known as the model regulator is investigated here as a robust steering controller for such yaw stabilization tasks in a driver-assist system. The yaw stability-enhancing steering controller is designed in the parameter space to satisfy a frequency-domain mixed sensitivity constraint. To evaluate the resulting controller design, a real-time hardware-in-the-loop simulator is developed. Steering tests with and without the controller in this hardware-in-the-loop setup allow the driver to see the effect of the proposed controller to improve vehicle-handling quality. The hardware-in-the-loop simulation setup can also be used for real-time driver-in-the-loop simulation of other vehicle control systems.